2021
DOI: 10.1177/0095399721996325
|View full text |Cite
|
Sign up to set email alerts
|

Social Services in Ethnically Mixed Cities: Street-Level Bureaucracy at the Crossroads of Ethno-National Conflict

Abstract: There is a paucity of research examining street-level bureaucracy in cities affected by ongoing ethnopolitical conflict. This study addresses this limitation by exploring the work of social workers in the public services of mixed cities in Israel. It shows the interconnection between ambiguous institutional policies, varying workers’ views of the role of social services, and changing discretion patterns. Findings also suggest that episodes of conflict escalation intensify staff ethnic sectarianism, as well as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…In addition, the study focuses on LGBTQ+ street-level bureaucrats, a population that is overlooked in the current representative bureaucracy and street-level bureaucracy literatures (Davidovitz, 2022b; Bishu & Kennedy, 2020). Furthermore, there is also limited research on street-level bureaucracy and representative bureaucracy in cities affected by ethno-political conflicts (Shwartz-Ziv & Strier, 2022; Strier et al, 2021). Our study, therefore, adds to these literatures as well.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the study focuses on LGBTQ+ street-level bureaucrats, a population that is overlooked in the current representative bureaucracy and street-level bureaucracy literatures (Davidovitz, 2022b; Bishu & Kennedy, 2020). Furthermore, there is also limited research on street-level bureaucracy and representative bureaucracy in cities affected by ethno-political conflicts (Shwartz-Ziv & Strier, 2022; Strier et al, 2021). Our study, therefore, adds to these literatures as well.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have also shown that when a violent national event occurs, feelings of suspicion and fear increase among colleagues, and they limit their interactions. Moreover, in conflict zones, social workers often experience direct and secondary trauma during their practice and deal with feelings of fear and anxiety (Ramon et al, 2006; Strier et al, 2021; Truell, 2019).…”
Section: Social Work Within the Context Of Political Conflictsmentioning
confidence: 99%
“…In recent decades, in response to the global refugee crisis and conflicts between or within countries, the social work profession has paid increased attention to how political conflicts affect its practice, policy, and training (Campbell et al, 2018; Ramon, 2021; Strier et al, 2021). Scholars have called on the social work profession to take an active critical role within these contested settings, particularly with regard to creating solidarity and alliances in divided communities and promoting peace and conflict resolution (Moshe-Grodofsky, 2019; Truell, 2019).…”
Section: Introductionmentioning
confidence: 99%